Genome-Wide Analysis of Ascorbic Acid Metabolism Related Genes in Fragaria × ananassa and Its Expression Pattern Analysis in Strawberry Fruits - Liu, Huabo; Wei, Lingzhi; Ni, Yang; Chang, Linlin; Dong, Jing; Zhong, Chuanfei; Sun, Rui; Li, Shuangtao; Xiong, Rong; Wang, Guixia; Sun, Jian; Zhang, Yuntao; et al. (Frontiers in Plant Science, 2022)
Ascorbic acid (AsA) is an important antioxidant for scavenging reactive oxygen species (ROS), it is essential for human health. Strawberry (Fragaria × ananassa) fruits are rich in AsA. In recent years, strawberry has been regarded as a model for non-climacteric fruit ripening. However, in contrast to climacteric fruits, such as tomato, the regulatory mechanism of AsA accumulation in strawberry fruits remains largely unknown. In this study, we firstly identified and analyzed 125 AsA metabolism related genes from cultivated strawberry ‘Camarosa’ genome. The expression pattern analysis in fruits at different ripening stages showed that the AsA biosynthetic-related genes in D-mannose/L-galactose pathway were down-regulated remarkably during fruit ripening which was opposite to the increasing AsA content in fruits. While the D-galacturonate reductase gene (GalUR) in the D-Galacturonic acid pathway, was extremely up-regulated in strawberry receptacles during fruit ripening. The FaGalUR gene above belongs to aldo-keto reductases (AKR) superfamily, and has been proposed to participate in AsA biosynthesis in strawberry fruits. In order to explore whether there are other genes in AKR superfamily involved in regulating AsA accumulation during strawberry fruit ripening, we further implemented a genome-wide analysis of the AKR superfamily using octoploid strawberry genome. A total of 80 FaAKR genes were identified from the genome and divided into 20 subgroups based on phylogenetic analysis. These FaAKR genes were unevenly distributed on 23 chromosomes. Among them, nine genes showed increasing expression in receptacles as fruit ripening, and notably, FaAKR23 was the most dramatically up-regulated FaAKR genes in receptacles. Compare with fruits at green stages, its expression level increased by 142-fold at red stages. In particular, the FaAKR23 was the only FaAKR gene which was significantly up-regulated by abscisic acid (ABA) and suppressed by nordihydroguaiaretic acid (NDGA, an ABA biosynthesis blocker), indicating FaAKR23 might play important roles in ABA-mediated strawberry fruit ripening. In a word, our study provides useful information on the AsA metabolism during strawberry fruit ripening, and will help understand the mechanism of AsA accumulation in strawberry fruits.